2004
DOI: 10.1074/jbc.c400337200
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Blue Animal Pigments Based on Frizzled and Kringle Protein Domains

Abstract: The nature of coloration in many marine animals remains poorly investigated. Here we studied the blue pigment of a scyfoid jellyfish Rhizostoma pulmo and determined it to be a soluble extracellular 30-kDa chromoprotein with a complex absorption spectrum peaking at 420, 588, and 624 nm. Furthermore, we cloned the corresponding cDNA and confirmed its identity by immunoblotting and mass spectrometry experiments. The chromoprotein, named rpulFKz1, consists of two domains, a Frizzled cysteine-rich domain and a Krin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…Our search demonstrated that Fz-CRD and KR domains are ubiquitous among cnidarians, yet only eight protein sequences were discovered that fall within the same clade and have the same domain structure as rpulFKz1 (Bulina et al, 2004). Among these proteins, the sequence that belongs to Cassiopea xamachana has motifs that mostly match Cassio Blue tryptic digests (Phelan et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Our search demonstrated that Fz-CRD and KR domains are ubiquitous among cnidarians, yet only eight protein sequences were discovered that fall within the same clade and have the same domain structure as rpulFKz1 (Bulina et al, 2004). Among these proteins, the sequence that belongs to Cassiopea xamachana has motifs that mostly match Cassio Blue tryptic digests (Phelan et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…This may be explained by their low coverages in the photos (coverages of 0.2% for green, and 0.5% for blue). Indeed, within the circalittoral shelf, where coralligenous reefs grow, chlorophyll organisms (including green algae) are less abundant because of a lack of light, and blue pigments are relatively rare in animal colouration 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The colour literature contains a large body of work on the physics and chemistry of colour production and blue colours have received considerable research attention (Goodrich & Reisinger, 1953;Dyck, 1971;Veron, 1973;Rohrlich, 1974;Byers, 1975;Filshie, Day & Mercer, 1975;Kazlauskas et al, 1982;Blanquet & Phelan, 1987;Wilson, 1987;Goda & Fujii, 1995Brink & Lee, 1999;Vukusic et al, 2001;Kinoshita, Yoshioka & Kawagoe, 2002;Bulina et al, 2004;Vukusic & Hooper, 2005;Watanabe et al, 2005;Doucet et al, 2006;Bagnara, Fernandez & Fujii, 2007;Simmonis & Berthier, 2012). This research attention may reflect our curiosity about brilliantly blue-coloured animals and the potential that colourproducing mechanisms have for biomimetic industrial applications.…”
Section: The Production Of Blue Coloursmentioning
confidence: 99%
“…carotenoids), but blue pigments are rare, perhaps because they necessitate more complex chemistry. For example, the blue pigment compound of the bryozoan Rhizostoma pulmo requires a very long and highly polarized chain of single-double alternating carbon bonds (Bulina et al, 2004). When they are present blue pigments are more likely to be found in the extracellular matrix for example in the copepod Pontella fera, the crayfish Procambarus clarkii and the abalone Haliotis discus hannai (Herring, 1965;Cheesman, Lee & Zagalsky, 1967;Milicua et al, 1985).…”
Section: Pigmentary Bluesmentioning
confidence: 99%